On the proportion of cancer stem cells in a tumour - Johnston, Matthew D.; Maini, Philip K.; Jonathan Chapman, S.; Edwards, Carina M.; Bodmer, Walter F. (Journal of theoretical biology, 2010)
It is now generally accepted that cancers contain a sub-population, the cancer stem cells (CSCs), which initiate and drive a tumour’s growth. At least until recently it has been widely assumed that only a small proportion of the cells in a tumour are CSCs. Here we use a mathematical model, supported by experimental evidence, to show that such an assumption is unwarranted. We show that CSCs may comprise any possible proportion of the tumour, and that the higher the proportion the more aggressive the tumour is likely to be.